Childhood florid follicular hyperplasia with immunoglobulin light‐chain restriction in the gastrointestinal tract. Issue 6 (30th October 2014) - Martinez‐Lopez, Azahara; Montes‐Moreno, Santiago; Ramos, Rafael; Afonso‐Martin, Juan Luis; Mazorra, Francisco; Gonzalez de Villambrosia, Sonia; Batlle, Ana; Grogan, Thomas M; Piris, Miguel Angel
<x xml:space="preserve">Abstract</x> Aims Immunoglobulin light‐chain expression is used routinely as an indirect marker of clonality for recognizing B cell lymphoproliferative disorders. Methods and results Here we describe four floral follicular hyperplasia cases in the gastrointestinal tract (appendix and rectum) of children (4 to 6 years). Immunohistochemical studies revealed lambda light‐chain restriction that was associated with polyclonal IgH pattern. Clinical features and follow‐up of the patients did not reveal any other systemic symptoms, laboratory abnormalities or organ alterations. Conclusions Recognition of this phenomenon is useful in the diagnosis of nodular lymphoid hyperplasia of the gastrointestinal tract, for avoiding overdiagnosis of lymphoid malignancies, and raises concerns that the identification of light‐chain restriction is not necessarily a marker of monoclonality.